2018
DOI: 10.3847/2041-8213/aaca92
|View full text |Cite
|
Sign up to set email alerts
|

MESSENGER Observations of Rapid and Impulsive Magnetic Reconnection in Mercury's Magnetotail

Abstract: The nature of magnetic reconnection in planetary magnetospheres may differ between various planets. We report the first observations of a rapidly evolving magnetic reconnection process in Mercury’s magnetotail by the MESSENGER spacecraft. The reconnection process was initialized in the plasma sheet and then evolved into the lobe region during a ∼35 s period. The tailward reconnection fronts of primary and secondary flux ropes with clear Hall signatures and energetic electron bursts were observed. The reconnect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Mass, energy, and magnetic flux are transported from Mercury's dayside magnetopause to its nightside magnetotail via an Earth-like Dungey cycle (Imber & Slavin, 2017;Slavin et al, 2010). The cycle is completed by the return flow of mass, energy, and flux toward Mercury driven by magnetic reconnection in Mercury's PS (DiBraccio, Slavin et al, 2009;Smith et al, 2017;Sun et al, 2015;Sundberg et al, 2012;Zhong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Mass, energy, and magnetic flux are transported from Mercury's dayside magnetopause to its nightside magnetotail via an Earth-like Dungey cycle (Imber & Slavin, 2017;Slavin et al, 2010). The cycle is completed by the return flow of mass, energy, and flux toward Mercury driven by magnetic reconnection in Mercury's PS (DiBraccio, Slavin et al, 2009;Smith et al, 2017;Sun et al, 2015;Sundberg et al, 2012;Zhong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This also correlates with shifts in statistical field distributions (Poh et al, ), dipolarizations (Dewey et al, ), and the distribution of energetic electrons (Baker et al, ) and their precipitation onto the surface (Lindsay et al, ). In addition, Zhong et al () recently reported the first observations of an active reconnection site in Mercury's magnetotail, during which the spacecraft was located ∼0.5 R M dawnward of midnight.…”
Section: Introductionmentioning
confidence: 99%
“…A key signature for identifying active reconnection is the quadrupole Hall magnetic field structure, resulting from ion‐electron decoupling in the ion diffusion region (Sonnerup, 1979). In the reconnection events during orbits 503 and 877 (Zhong et al., 2018, 2020a), the MESSENGER south‐to‐north crossed the tail current sheet and observed a significant positive‐to‐negative bipolar feature in the out‐of‐plane magnetic field component B M with overall negative B N . Another key reconnection feature is the formation of multiple flux rope (FR) structures.…”
Section: Reconnection Events In Mercury's Magnetotailmentioning
confidence: 99%